Educators' Observations of Children's Display of Problematic Sexual Behaviors in Educational Settings. Issue 1 (2nd January 2018) - Ey, Lesley-Anne; McInnes, Elspeth
ABSTRACT: It is widely recognized that children are sexual beings and their sexual development begins at an early age. Recently, there has been some concern about children's sexual behavior in educational settings (Knowles 2014). Obtaining a better understanding of what behaviors children are displaying in these settings provides valuable information to inform teacher education in this area as well as support systems for children. One hundred and seven Australian educators from care organizations, preschools, and government, independent, and Catholic primary schools participated in an extensive online questionnaire in relation to their understanding of and experiences with children's problematic sexual behaviors and their management strategies. Results found that 40.8% of educators had observed children displaying problematic sexual behavior in their educational setting. Educators' descriptions of their observations variously involved children physically acting out sexually with other children, sexually harassing other children, verbally attempting to coerce other children to participate in sexual behavior, and individual displays of sexual behavior. A minority described behaviors that are considered developmentally typical but are not socially acceptable in an educational setting. These results indicate that there is a need for educator training, child education, and support services to enable an early intervention and prevention strategy to support the well-being of children.